THE INFLUENCE OF THE HERFANI WATERBOOM TOURISM OBJECT ON THE SOCIO-ECONOMIC TRICKLE DOWN EFFECT OF THE LEOK II VILLAGE COMMUNITY, BUOL DISTRICT - Relina, Riri; Sahwan, Sahwan (STIE Mujahidin Tolitoli Development Economics Study Program, 2024)
The problem examined in this research is how much influence the Herfani Waterboom tourist attraction has on the socio-economic trickle down effect of the community in Leok II sub-district, Buol Regency. The analytical method used in this research is a quantitative method with an associative approach. The associative quantitative data in this research amounted to 30 people. The data collection techniques used are observation, interviews, questionnaires and documentation techniques. This research aims to determine the direction of water boom tourism on the trickle down effect in Leok II Village, Buol Regency. This research uses associative quantitative methods. The data source is primary data obtained through questionnaires and documentation related to this research. The data analysis technique uses statistical calculations using the SPSS 16 application. The results of the research show that Waterboom Tourism has a significant effect on Trickle Down Effcet in Leok II Village, Buol Regency.